Case report and literature review: Rare male aggressive angiomyxoma of the scrotum - Chen, Yue; Wei, YaPing; Chang, Hong; Yu, ChunKai (Frontiers in Surgery, 2022)
Aggressive angiomyxoma (AAM) is an uncommon locally infiltrative tumor that frequently occurs in the pelvic soft tissues of female patients; it has a high rate of local recurrence. However, AAM is extremely rare in males. Herein, we present the case of a 70-year-old man with a gradually enlarging painless mass in the scrotum. The patient underwent local excision of the scrotal AAM, with no local relapse after 17 months of follow-up. In addition to the present case, the clinicopathological features of males with AAM reported in literature (to the best of our knowledge) are discussed in this report. The literature review revealed that the gross morphology, clinical process, and histopathology of AAM in males resemble those of AAM in females. In particular, estrogen receptor/progesterone receptor has been shown to be expressed in male patients, which may provide an option for hormone therapy. Moreover, in males, a lower recurrence rate has been observed after surgery to remove the tumor. However, more data are needed to validate this observation. This report emphasizes the importance of considering AAM as the differential diagnosis of myxoid neoplasms in male genital areas.